IL-21 Is an Accomplice of PD-L1 in the Induction of PD-1-Dependent Treg Generation in Head and Neck Cancer - Zhao, Yi; Zhang, Zhiyu; Lei, Wenbin; Wei, Yi; Ma, Renqiang; Wen, Yihui; Wei, Fanqin; Fan, Jun; Xu, Yang; Chen, Lin; Lyu, Kexing; Lin, Hanqing; et al. (Frontiers in Oncology, 2021)
Regulatory T cells (Tregs) are immunosuppressive cells involved in antitumor immunity. However, the regulation of Treg generation by inflammation in the tumor microenvironment has not been carefully investigated. Here, we demonstrated that IL-21-polarized inflammation was enriched in the tumor microenvironment in head and neck squamous cell carcinoma (HNSCC) and that IL-21 could promote PD-L1-induced Treg generation in a PD-1-dependent manner. Moreover, generated Tregs showed a greater ability to suppress the proliferation of tumor-associated antigen (TAA)-specific T cells than naturally occurring Tregs. Importantly, an anti-PD-1 antibody could inhibit only Treg expansion induced by clinical tumor explants with high expression of IL-21/PD-L1. In addition, neutralizing IL-21 could enhance the anti-PD-1 antibody-mediated inhibitory effect on Treg expansion. Furthermore, simultaneous high expression of IL-21 and PD-L1 was associated with more Treg infiltrates and predicted reduced overall and disease-free survival in patients with HNSCC. These findings indicate that IL-21 in the tumor microenvironment may promote PD-L1-induced, Treg-mediated immune escape in a PD-1-dependent manner and that an IL-21 neutralization strategy may enhance PD-1 blockade-based antitumor immunotherapy by targeting Treg-mediated immune evasion in patients with high expression of IL-21 and PD-L1.